The Big Thaw Policy, Governance, and Climate Change in the Circumpolar North - Zubrow, Ezra B. W.; Meidinger, Errol; Connolly, Kim Diana (SUNY Press Open Access; SUNY series in Environmental Governance: Local-Regional-Global Interactions, 2019)
Climate change, one of the drivers of global change, is controversial in political circles, but recognized in scientific ones as being of central importance today for the United States and the world. In The Big Thaw, the editors bring together experts, advocates, and academic professionals who address the serious issue of how climate change in the Circumpolar Arctic is affecting and will continue to affect environments, cultures, societies, and economies throughout the world. The contributors discuss a variety of topics, including anthropology, sociology, human geography, community economics, regional development and planning, and political science, as well as biogeophysical sciences such as ecology, human-environmental interactions, and climatology.